The Influence of Parenting Patterns on Learning Motivation of Students with Learning Difficulties - Al Shaffaat Ronvy; Hafiz Hidayat; Della Oktania (Jurnal Counseling Care, 2025)
This study aims to analyze the influence of parenting styles on the learning motivation of students with learning difficulties. The research subject is a fourth-grade male student who has experienced learning difficulties and has repeated a grade twice. His parents work as market traders, limiting their ability to provide supervision and academic support at home. This lack of parental involvement negatively impacts the child’s learning motivation, leading to frequent absences and low participation in academic activities. This research employs a case study method with a qualitative approach. Data collection was carried out through observations at school and home, interviews with teachers and parents, and analysis of attendance records and academic performance. The findings indicate that permissive parenting and lack of parental supervision contribute to low learning motivation. The absence of tailored educational interventions further exacerbates the student’s academic struggles. Therefore, strategies such as tutoring programs, enhanced communication between schools and parents, and more targeted educational interventions are needed to provide better academic support for students with learning difficulties. Keywords: Parenting Style, Learning Motivation, Learning Difficulties, Special Education